Regulating Commission-Based Financial Advice: Evidence from a Natural Experiment - Sokolinski, Stanislav (Journal of Financial and Quantitative Analysis, 2023)
Abstract Do limitations on commissions paid to financial advisers reduce prices of financial products and stimulate investment? I examine these questions by estimating the causal effects of regulating commissions for mutual fund distribution. I exploit the unique institutional setting in Israel and the 2013 policy change when the government reduced commissions differently for different fund types. The reform led to a major decline in fund expense ratios and a consequent increase in fund flows. Funds with price-sensitive investors experienced 35% larger inflows. I interpret these results as investor responses to price competition fostered by a reduction in distribution costs.